Knowledge gaps and bibliographical revision about descriptions of free-swimming anuran larvae from Brazil - Provete, Diogo Borges; Garey, Michel Varajão [UNESP]; Da Silva, Fernando Rodrigues; Jordani, Mainara Xavier [UNESP] (My University, 2012)
Research on tadpole morphology has grown rapidly in recent decades, but many larval anurans remain unknown. We made a literature survey of all studies that describe free-swiming larvae of anuran species occurring in Brazil in order to identify major gaps and provide a searchable bibliographical source about these descriptions. We found that 61.25% of tadpoles of species with free-swiming larvae have already been described. We hope that this paper will foster future tadpole descriptions by providing easy access to the literature. © NwjZ, Oradea, Romania, 2012.
Keywords: Anura; Herpetology; Literature survey; Tadpoles